Influence of Fermented Vegetable Consumption on Gut Microbiome Diversity. (7th June 2021) - Ullrich, Sina; Thriene, Kerstin; Binder, Nadine; Amend, Lena; Strowig, Till; Michels, Karin
Abstract: Objectives: The effects of fermented foods on the gut microbiome are of great interest, yet evidence regarding its potential to increase gut microbial diversity, a measure likely associated with health, is lacking. Therefore, we analyzed the microbial composition (bacteria and yeasts) of commercially available fermented vegetables. Furthermore, we conducted a pilot study to assess the feasibility of studying effects of regular consumption of fermented vegetables on the gut microbiome. Methods: Six healthy male volunteers (age: 25.5 ± 2.9yrs, BMI: 24.3 ± 1.2kg/m 2 ) participated in a randomized crossover trial, with two 2-week intervention phases each of which was preceded by a 2-week washout phase. Participants consumed 150g/d of either sauerkraut (intervention 1) or a variety of six different fermented vegetables (intervention 2). We used 16S rRNA sequencing to assess the effects of each dietary regime on the composition, diversity and dynamics of the gut microbiome, as well as the composition and diversity of the fermented vegetable microbiome. Results: Lactobacillus was the dominant genus in all fermented vegetables; still, the alpha diversity, richness and evenness of the microbiota differed substantially among the different products. Among our study participants, we observed an increase in alpha diversity (Shannon index) after both, consumption of sauerkraut (pre intervention: 3.31 ± 0.74, post intervention: 3.58 ± 0.68) and the selection of fermented vegetables (pre: 3.60 ± 0.93, post: 3.84 ± 0.81). However, the results did not reach statistical significance, due to the high inter- and intra-individual variability as evaluated by beta diversity of the gut microbial communities. Conclusions: A longer-term intervention study with fermented vegetables and/or sauerkraut seems feasible. Consumption of fermented vegetables appears to increase the diversity of the gut microbiome, even after a relatively short period of time. However, further studies with a larger sample size are warranted to verify our observations. Funding Sources: Institutional budget.